Pengembangan Center of Honey Kampung Madu Lumbang Kabupaten Probolinggo - Savitri, Emma; Prayitno, Agung; Hadi, Syamsul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Lumbang Honey is one of the featured products owned by Lumbang, Probolinggo, East Java. As a featured product, the legality has been issued by the Probolinggo District Government through Probolinggo Regent Decree number 030/1134/426.12/2013. Lumbang honey is supported by 10 Forest Farmer Groups with honey production of 6,206 kg per month in 2014. Although the amount of honey production is very abundant, Lumbang honey has not been able to compete with commercial honey products on the market. This is because the quality and price of Lumbang honey is very diverse. Therefore, The Center of Honey "Kampung Madu" was established in Lumbang Village, Probolinggo. The purpose of Kampung Madu are as a place to produce premium quality of honey as well as a place for marketing and honey-related education to the community. The method is by approaching the technology application and product standardization as well as assistance in strengthening the farmer institutional management. The results of the assistance, Kampung Madu has been able to produce an average of 900 kg of premium quality of honey per month with the brand "Madu Madakaripura" which has fulfilled the water content in accordance with SNI 8664 : 2018 which is less than 22% and has obtained a PIRT certificate. In terms of prices, there is an increase in the price of honey to 500 % of the raw honey obtained from farmers. From the aspect of strengthening institutional management, there have been 30 farmers in the District of Lumbang who are members of the Cooperation of HIMATERA in the honey division. The cooperation has a role in helping the farmers in providing capital and facilities.